Leading sectors, multiplier effects, and economic spillovers among the islands of East Nusa Tenggara Province - Taena, Werenfridus; Klau, Anggelina Delviana; Kase, Marce Sherly; Blegur, Fried Markus Alung; Afoan, Felisisima; Buan, Febrya Christin Putri Handayani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
Regional economic disparities and fragmented inter-island linkages remain key challenges in East Nusa Tenggara (NTT), one of Indonesia’s archipelagic provinces with diverse resource endowments. This study analyzes the structure and dynamics of NTT’s regional economy by identifying its leading sectors through intersectoral linkage analysis, estimating the magnitudes of multiplier effects, and examining spillover effects across the province’s major islands. The research utilizes the 2016 Input–Output Table of NTT Province and the accumulated Gross Regional Domestic Product (GRDP) data of regencies and cities across the Timor, Flores, and Sumba islands for the 2016–2023 period. Analytical methods include linkage analysis, multiplier effect estimation, and the Vector Error Correction Model (VECM). The results show that agriculture, manufacturing, electricity, trade, and transportation constitute the leading sectors due to their strong forward and backward linkages. At the same time, agriculture and manufacturing also generate the largest multiplier effects. These sectors further create significant inter-island spillover effects, characterized by spread effects between Sumba–Timor, Sumba–Flores, and Timor–Sumba, and backwash effects between Timor–Flores and Flores–Sumba. The findings highlight that strengthening productive linkages in agriculture and manufacturing is vital for enhancing spatial equity and promoting inclusive regional growth. Conceptually, this study contributes to the literature by integrating intersectoral, multiplier, and spillover analyses to explain spatial economic interdependence in archipelagic regions and by offering practical policy implications for fostering sustainable inter-island integration in NTT Province.